Margin of seimic design for mechanical structures with gaps through experimental investigation - Yusuke MINAKAWA; Tadashi IIJIMA; Naotomo MARUYAMA (Nihon Kikai Gakkai ronbunshu)
Seismic design for equipment and piping systems typically conducts linear evaluations using maximum response accelerations or response spectra of structures. However, gaps exist between structures and support structures in these systems, which can affect their response behavior. This study aimed to confirm the margin between the linear evaluation and the evaluation that considers the effects of these gaps. Vibration experiments were conducted on a beam and support structures with gaps to measure strain and acceleration at the center of a test specimen. The experiment conditions were varied by changing the input acceleration levels and gap sizes. The results indicated that increasing the gap size led to a decrease in strain and an increase in acceleration. To evaluate the effects of gaps, a strain response factor was defined as the ratio of the maximum input acceleration to the strain, and a normalized gap was defined as the ratio of the maximum input displacement to the gap. The relationship between the strain response factor and the normalized gap can be divided into five characteristics, and it was indicated that increasing the normalized gap led to a decrease in the strain response factor. Additionally, an effective acceleration was defined in proportion to the strain, and an effective acceleration response factor was defined to be the ratio of the maximum input acceleration to the effective acceleration. The effective acceleration response factor without a gap was obtained from the response spectrum using input wave. A proposed method was developed to explain the observed behaviors of five characteristics between the effective acceleration response factor and the normalized gap. The evaluation results using the proposed method were compared with the experimental results. The comparison results indicated that the evaluation results can reproduce the experimental results. Therefore, the proposed method provided a way to confirm the mergin between the linear evaluation and the consideration of gap effects in linear seismic design for equipment and piping systems.